2011
DOI: 10.1007/s10705-011-9452-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving process-based estimates of N2O emissions from soil using temporally extensive chamber techniques and stable isotopes

Abstract: Nitrous oxide (N 2 O) is an important greenhouse gas that is emitted from soil, but obtaining precise N 2 O source and sink strength estimates has been difficult due to high spatial and temporal flux variability and a poor understanding of the mechanisms controlling fluxes. Tools that improve our ability to quantify trace gas fluxes from soil and constrain annual budgets are therefore needed. Here we describe an improved chamber-based sampling system that continuously traps evolving soil gases onto molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Although an isotope effect during fungal denitrification in the N α and N β positions was not reported by Sutka et al,14 14 also observed markedly large variation in δ 15 N of −74.7 to −6.6 ‰, which was attributed to the potential for diffusion of substrates into the cell to limit expression of the enzymatic fractionation during NO reduction in fungi. 48 Indeed, a correlation between δ 15 N and the rate constant was observed, which is consistent with diffusion control of both the reaction rate and the net isotopic fractionation. Consequently, the contrast in the direction and magnitude of fractionation factors for N 2 O production between the entire fungal denitrification process and those of purified fungal P450nor may be the result of variable expression of the small fractionation imposed by diffusion of substrates into and out of cells.…”
Section: ■ Discussionsupporting
confidence: 69%
“…Although an isotope effect during fungal denitrification in the N α and N β positions was not reported by Sutka et al,14 14 also observed markedly large variation in δ 15 N of −74.7 to −6.6 ‰, which was attributed to the potential for diffusion of substrates into the cell to limit expression of the enzymatic fractionation during NO reduction in fungi. 48 Indeed, a correlation between δ 15 N and the rate constant was observed, which is consistent with diffusion control of both the reaction rate and the net isotopic fractionation. Consequently, the contrast in the direction and magnitude of fractionation factors for N 2 O production between the entire fungal denitrification process and those of purified fungal P450nor may be the result of variable expression of the small fractionation imposed by diffusion of substrates into and out of cells.…”
Section: ■ Discussionsupporting
confidence: 69%
“…When discussing model sensitivity and uncertainty issues it is also important to be cognizant of issues in the underlying field trial datasets. Field measurements of N 2 O are very challenging due to emissions variability on extremely fine spatial (Li et al ., ) and temporal (Jørgensen et al ., ; van der Weerden et al ., ) scales, and studies based on sampling at weekly or every‐other‐week frequency (as was the case for all N 2 O studies in our dataset) are vulnerable to systematic biases of up to 20% and 60%, respectively (Parkin, ; Smemo et al ., ). Additionally, small‐scale field trials do not necessarily reflect imperfections in agronomic management (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…All the four algorithms under-simulated daily or seasonal N 2 O emissions in 2003 as discussed above. While in other three years, all the algorithms oversimulated N 2 O emissions compared to the measured data (Tables 3 and 4), possibly due to missing measured N 2 O emission peaks using chamber method in the field experiments (Parkin, 2008;Smemo et al, 2011). Wang et al (2013) found that the chamber method measured N 2 O emissions were general lower by 17e20% than the measured N 2 O emissions using eddy covariance method in a cotton field in Shanxi, China.…”
Section: Comparisons Of the Different N 2 O Emission Algorithms Basedmentioning
confidence: 92%